2022
DOI: 10.7759/cureus.22194
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beta-Human Chorionic Gonadotropin (β-hCG) Levels as a Predictor of Successful Medical Management of Ectopic Pregnancy

Abstract: The early diagnosis of ectopic pregnancy is essential in determining the appropriate therapeutic approach. This study demonstrates the important factors considered in the prediction of a successful medical treatment, which will, in turn, improve the quality of patient counseling and guidance prior to the initiation of the treatment. MethodsThis was a retrospective cohort study of 58 ectopic pregnancies that were treated medically with methotrexate in Bahrain Defense Force (BDF) Hospital from January 2016 to Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Similarly, in our study the mean baseline ßHCG levels were lower in the successful group (882.35) than the unsuccessful group (1083.99), but there were no significant differences between the two groups ( p = 0.098). The sample size in our study was greater than Keshta's 11 study (690 vs. 58, respectively). In our study, baseline ßHCG cut off value for successful treatment was 504.5 with 58% sensitivity and 51% specificity.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Similarly, in our study the mean baseline ßHCG levels were lower in the successful group (882.35) than the unsuccessful group (1083.99), but there were no significant differences between the two groups ( p = 0.098). The sample size in our study was greater than Keshta's 11 study (690 vs. 58, respectively). In our study, baseline ßHCG cut off value for successful treatment was 504.5 with 58% sensitivity and 51% specificity.…”
Section: Discussionmentioning
confidence: 61%
“…In keshta,s 11 study, The mean baseline ßHCG levels were significantly lower in the successful group (1403) compared with the unsuccessful group (2845). The baseline ßHCG cut off value for successful treatment in Keshta's 11 study was 2141 with 72% sensitivity and 75% specificity. Similarly, in our study the mean baseline ßHCG levels were lower in the successful group (882.35) than the unsuccessful group (1083.99), but there were no significant differences between the two groups ( p = 0.098).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Mean age was noted 30.23+5.16 years in successful group and 31.07 +4.33 years in failed treatment group with p value 0.362 in a study conducted by Lee JH et al 24 Another study by Keshta AS et al showed that patients in successful group had parity 2 (0-9) and 1 (0-5) in failure group p value 0.73, not statistically significant comparable with our results. 25 The most predictive variable of success of medical treatment is pretreatment β-hCG level. In our study, the difference between the mean pre-treatment serum β-hCG level in the success and failure groups was statistically significant i.e.,1491.79 ± 1094.69 vs. 2701.50 ± 1417.28 IU/L with p =0.038.…”
Section: Discussionmentioning
confidence: 99%